Influencia de la cultura en la experiencia del cáncer - Die Trill, María (Psicooncología, 2003)
Optimal cancer care should integrate cultural variables that influence psychosocial adjustment to the disease and its treatments. This article describes some of the most important cultural variables that may affect an individual’s response to the disease: causal attributions to cancer; family members´ role in patient care; truth-telling practices; attitudes towards pain; and attitudes towards death and dying. The article is based on others previously published. Its main purpose is to increase medical staff’s awareness of the need to understand the culturally different cancer patient in societies in which increasing immigration rates oblige some individuals to treat and confront their illness in cultural environments that are unknown to them.